2018
DOI: 10.12659/msm.909870
|View full text |Cite
|
Sign up to set email alerts
|

Role of Strain Elastography and Shear-Wave Elastography in a Multiparametric Clinical Approach to Indeterminate Cytology Thyroid Nodules

Abstract: BackgroundIn thyroid nodules with indeterminate cytology, further clinical assessment aimed at ruling out malignancy is often mandatory. Ancillary imaging techniques and genetic mutation analysis can improve the risk stratification of such lesions, thereby facilitating the clinician’s decision to undertaken surgery or simple follow-up. The aim of this study was to evaluate the diagnostic performance of shear-wave elastography (SW), strain elastography (ELX 2/1), conventional ultrasound (US), contrast-enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
12
0
2
Order By: Relevance
“…RTE and SWE do not seem interchangeable but may be used complementary. Interestingly, when strain index, SWV, and BRAF mutation were considered together, Sp was enhanced, but Se was lower compared to US findings alone [68].…”
Section: Elastography: Place In Indeterminate Cytology Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…RTE and SWE do not seem interchangeable but may be used complementary. Interestingly, when strain index, SWV, and BRAF mutation were considered together, Sp was enhanced, but Se was lower compared to US findings alone [68].…”
Section: Elastography: Place In Indeterminate Cytology Resultsmentioning
confidence: 88%
“…Nondiagnostic and indeterminate cytology represent the great limitations of FNAC and gray-scale US can sometimes be poorly predictive. About half of these nodules can avoid surgery by performing a second biopsy [68]. There was one study that reported higher prevalence of cancer on repeat FNAB, maybe as a consequence of the class of high-risk nodules that underwent second FNAB [69].…”
Section: Elastography: Place In Indeterminate Cytology Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than its individual value, it is more important to know the frequency at which elastography reveals a level of suspicion for malignancy that differs from that estimated by US (B-mode) and to what extent this level is modified by elastography. Regarding this additional value of elastography specifically in nodules with indeterminate cytology, the results are not uniform (Trimboli et al 2015, Cantisani et al 2016, Bardet et al 2017, Azizi et al 2018, Gay et al 2018, Liu et al 2018, Ríos et al 2018. If obtained, elevated stiffness on elastography is considered a suspicious finding for malignancy but it must be remembered that readings may be low in non-papillary thyroid carcinomas.…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…Currently, there are many elastographic techniques used in clinical practice: shear wave elastography biplane method, point share wave elastography, strain/real-time elastography, respectively fibroscan. [12]. The method is non-invasive, completely painless for the patient and can be easily performed even during routine ultrasound examinations.…”
Section: Introductionmentioning
confidence: 99%